(untitled) (Journal of Economic Research & Business Administration, 2019)
Such topics as innovations, project management, and Agile are incredibly relevant in the context of scientific researches in the business community. However, an approach at the junction of these concepts not theoretically developed, as well as it turned out that there are not so many successful «best practices» of their correct usage and combining to obtain a cumulative synergetic effect. At the same time, the practice shows that many approaches to the agile philosophy are firmly rooted in mind and become an essential factor in the success of the projects and business initiatives. The purpose of this article is to study international experience in the implementation and application of methods of flexible human resources management. This article illustrates some of the profound changes that companies are making in their practices and describes the challenges they face in transitioning to flexible human resource management. Because HRM affects every aspect–and every employee-of the organization, its flexible transformation can be even more extensive (and more complex) than changes in other functions. Therefore, the following areas are considered: performance appraisal, training, team, independent decision-making, complex team dynamics, remuneration, recruitment, training and development, problems. It is shown that the introduction of a project management system is a necessary condition for the development of the company in a constantly changing environment. Due to the flexible approach to the implementation of the project management system, companies can develop a project management system for their needs and business needs. Particular attention is paid to the possibility of using flexible project management methodologies in different conditions. The obtained theoretical and practical results in the course of research can be used to expand the theoretical and methodological basis of the problem of the labor market and human capital management.